1961
DOI: 10.1071/ar9610889
|View full text |Cite
|
Sign up to set email alerts
|

Water and electrolyte changes in tropical Merino sheep exposed to dehydration during summer

Abstract: During three summers field studies were made of Merino wethers deprived of water while exposed to sun and to maximum air temperatures ranging from 84°F (29°C) to 10S°F (42°C) at Julia Creek, lat. 21° S. Evaporative cooling determined the rate and extent of water and electrolyte changes and produced a different pattern each year. Control of body temperature failed when 31% of body weight was lost by the end of 10 days without water. In hotter weather 5 days without water caused a 25% loss of body weight and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
40
2
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 0 publications
15
40
2
1
Order By: Relevance
“…The increased haematocrit values are consistent with what was observed also by other authors in Awassi sheep (Laden et al 1987;Ghanem et al 2008), Merino sheep (MacFarlane et al 1961) and goats (Hossainini-Hilali et al 1994), subjected to different regimens of water deprivation. This has also been reported by Hamadeh et al (2006) in Awassi sheep.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The increased haematocrit values are consistent with what was observed also by other authors in Awassi sheep (Laden et al 1987;Ghanem et al 2008), Merino sheep (MacFarlane et al 1961) and goats (Hossainini-Hilali et al 1994), subjected to different regimens of water deprivation. This has also been reported by Hamadeh et al (2006) in Awassi sheep.…”
Section: Discussionsupporting
confidence: 80%
“…Water deficiency leads to increased water reabsorption at the nephron level; consequently, increased urea reabsorption is expected as it is a highly permeable molecule. In other experiments conducted on Merino (MacFarlane et al 1961) and Yankasa sheep (Aganga et al 1989;Igbokwe 1993) similar results have been obtained. Laden et al (1987) also reported a gradual increase in urea concentrations in response to two and five days of water restriction in Awassi sheep.…”
Section: Discussionsupporting
confidence: 75%
“…The increased excretion of water through suppression of ADH in these hydrated sheep was undoubtedly enhanced by the increase in GFR. The opposite picture is seen in dehydration of sheep (Macfarlane, Morris, Howard, McDonald and Budtz-Olsen, 1961) and in acute and chronic fluid depletion in man and dog (Wesson, 1969) where GFR and renal plasma flow decrease, a condition which in addition to an increase in ADH activity would favour a reduction in water excretion.…”
Section: Efect Of Adh On Urine Flow and Gfrmentioning
confidence: 99%
“…And the study of water restriction have been reported by MACFARLANE et al [5][6][7] and BIANCA et al 8). But in our country, knowledge of the physiological changes occurring in fattening beef cattle in response to water restriction is limited.…”
mentioning
confidence: 99%